ANALYSIS OF THERMAL DISPERSION IN SELAT SEMBILAN WATERS, NORTH SUMATRA - Aziz, Amiral (BPPT)
Pangkalan Susu Coal Fire Steam Power Plants (CFSPP) are planned to build in Tanjung Pasir Village, Langkat Regency taking sea water as cooling condenser of power plants, and through it back into the sea. To explore the possibilities of re-entry of the circulation of hot water to the intake, it is necessary to study the termal dispersion within the framework of those plans. In this study, numerical modeling to determine termal distribution pattern that comes out from CFSPP outlet. From the study it could be concluded that with the given intake inlet ? discharge outfall design configuration and under the worst scenario, cooling water system of Pangkalan Susu unit 3 4 is safe i.e. re-circulation of warmcooling water will not happen. The Pangkalan Susu unit 3 4 will consume intact sea water (30.5oC). However, the Pangkalan Susu unit 1 2 will be influenced by the warm cooling system that may decrease its cooling system efficiency since its inlet is covered by shattered sea water (31.2oC ? 32.2oC).keywords : thermal dispersion, power plant. numerical modeling